Respiratory muscle specific warm-up and elite swimming performance. Issue 9 (1st November 2013) - Wilson, Emma E; McKeever, Tricia M; Lobb, Claire; Sherriff, Tom; Gupta, Luke; Hearson, Glenn; Martin, Neil; Lindley, Martin R; Shaw, Dominick E
Abstract : Background: Inspiratory muscle training has been shown to improve performance in elite swimmers, when used as part of routine training, but its use as a respiratory warm-up has yet to be investigated. Aim: To determine the influence of inspiratory muscle exercise (IME) as a respiratory muscle warm-up in a randomised controlled cross-over trial. Methods: A total of 15 elite swimmers were assigned to four different warm-up protocols and the effects of IME on 100 m freestyle swimming times were assessed.Each swimmer completed four different IME warm-up protocols across four separate study visits: swimming-only warm-up; swimming warm-up plus IME warm-up (2 sets of 30 breaths with a 40% maximum inspiratory mouth pressure load using the Powerbreathe inspiratory muscle trainer); swimming warm-up plus sham IME warm-up (2 sets of 30 breaths with a 15% maximum inspiratory mouth pressure load using the Powerbreathe inspiratory muscle trainer); and IME-only warm-up. Swimmers performed a series of physiological tests and scales of perception (rate of perceived exertion and dyspnoea) at three time points (pre warm-up, post warm-up and post time trial). Results: The combined standard swimming warm-up and IME warm-up were the fastest of the four protocols with a 100 m time of 57.05 s. This was significantly faster than the IME-only warm-up (mean difference=1.18 s, 95% CI 0.44 to 1.92, p<0.01) and the swim-only warm-up (mean difference=0.62 s, 95% CI 0.001 to 1.23, p=0.05). Conclusions: Using IME combined with a standard swimming warm-up significantly improves 100 m freestyle swimming performance in elite swimmers.